Intra-abdominal hypertension and abdominal compartment syndrome. Issue 6 (3rd December 2022) - De Waele, Jan J.
Abstract : Purpose of review: Intra-abdominal hypertension (IAH) has been acknowledged as an important contributor to organ dysfunction in critically ill patients, both in surgical and medical conditions. As our understanding of the pathophysiology evolves, risk factors are better recognized, preventive measures can now be implemented and therapeutic interventions tailored to the physiology of the patient. In the current review, we want to highlight developing insights in the epidemiology and treatment of patients with IAH and ACS. Recent findings: The impact of IAH and ACS on kidney function and other outcomes continues to draw attention in recent studies. New methods for IAP measurement are under development, and the search for biomarkers to detect IAH or ACS continues. In conditions wherein IAH and ACS are common, recent studies allow better prevention and treatment of these conditions, based on the contemporary ICU management consisting of IAP measurement, judicious fluid resuscitation and decompressive laparotomy where necessary. Surgical treatment options including open abdomen therapy continue to be improved with demonstrable impact on outcomes. Summary: In this manuscript, we provide an overview of recent insights and developments in the epidemiology, monitoring and treatment of patients with IAH and/or ACS.